Activation of thromboxane A2 receptors mediates endothelial dysfunction in diabetic mice. (19th May 2017) - Xie, Xiaona; Sun, Wanchun; Wang, Jun; Li, Xiaoou; Liu, Xiaofeng; Liu, Ning
ABSTRACT: Background : Diabetes is one of high-risk factors for cardiovascular disease. Improvement of endothelial dysfunction in diabetes reduces vascular complications. However, the underlying mechanism needs to be uncovered. This study was conducted to elucidate whether and how thromboxane A2 receptor (TPr) activation contributes to endothelial dysfunction in diabetes. Methods and Results : Exposure of human umbilical vein endothelial cells (HUVECs) to either TPr agonists, two structurally related thromboxane A2 (TxA2 ) mimetics, significantly reduced phosphorylations of endothelial nitric oxide synthase (eNOS) at Ser 1177 and Akt at Ser 473 . These effects were abolished by pharmacological or genetic inhibitors of TPr. TPr-induced suppression of eNOS and Akt phosphorylation was accompanied by upregulation of PTEN (phosphatase and tension homolog deleted on chromosome 10) and Ser 380 /Thr 382/383 PTEN phosphorylation. PTEN-specific siRNA restored Akt–eNOS signaling in the face of TPr activation. The small GTPase, Rho, was also activated by TPr stimulation, and pretreatment of HUVECs with Y27632, a Rho-associated kinase (ROCK) inhibitor, rescued TPr-impaired Akt–eNOS signaling. In mice, streptozotocin-induced diabetes was associated with aortic PTEN upregulation, PTEN-Ser 380 /Thr 382/383 phosphorylation, and dephosphorylation of Akt (at Ser 473 ) and eNOS (at Ser 1177 ). Importantly, administration of TPr antagonist blocked these changes. Conclusion : We conclude that TPr activation impairs endothelial function by selectively inactivating the ROCK–PTEN–Akt–eNOS pathway in diabetic mice.